2005
DOI: 10.1002/pssc.200460819
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale flux pinning sites in high‐ T c superconductors

Abstract: PACS 74.25.Qt, 74.40.+k, 74.81.Bd Ideal flux pining centres in high-T c superconductors should be of nanometre size as the coherence length, ξ, is so small. Therefore, the optimisation of high-T c superconductor samples concerning high critical current densities and high flux pinning has to take place in the nanometre range. An important goal of the current research is to find specific preparation strategies to create such ideal flux pining sites already during the sample processing. By means of AFM and STM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Figure 1(b) illustrates a lamellae structure obtained in the SEG sample, similar to the patterns observed in NEG samples earlier. 2,7) The shape of the structure suggests that it rather consists of chains of aligned clusters. Measurements performed by energy dispersive X-ray analysis in a transmission electron microscope (TEM-EDX) confirmed that, 9) similar to NEG, the (Sm,Eu,Gd)/Ba-ratio oscillates around the stoichiometric 1 : 2 ratio across the lamellae.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1(b) illustrates a lamellae structure obtained in the SEG sample, similar to the patterns observed in NEG samples earlier. 2,7) The shape of the structure suggests that it rather consists of chains of aligned clusters. Measurements performed by energy dispersive X-ray analysis in a transmission electron microscope (TEM-EDX) confirmed that, 9) similar to NEG, the (Sm,Eu,Gd)/Ba-ratio oscillates around the stoichiometric 1 : 2 ratio across the lamellae.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] Since the asgrown surfaces of the samples were usually too rough to achieve good scanning results, the samples were mechanically polished prior to scanning, either dry from 12 to 0.5 mm diamond paper or wet from 320 grain SiO paper to 4000 grain SiO paper and then from 3 mm diamond polishing solution down to 40 nm colloidal silica (Struers OP-S). 7) After that, the samples were cleaned for several minutes in acetone in an ultrasonic bath and then for several minutes in an isopropanol bath. The sample surfaces were mechanically polished prior to scanning, and in some cases, an etching procedure was applied.…”
Section: Methodsmentioning
confidence: 99%
“…The surfaces of light rare earth element-based high-T c superconductors with the composition (LRE)Ba 2 Cu 3 O x (with LRE = light rare earths, e.g. Nd, Eu, Gd, Sm) revealed the presence of pronounced nanostripe structures with periodicities varying between 10 and 60 nm [1][2][3][4]. Such nanostripes or nanoclusters were found by means of atomic force microscopy (AFM), scanning tunnelling microscopy (STM) and transmission electron microscopy (TEM) investigations in a variety of (LRE)Ba 2 Cu 3 O x superconductors; namely in melttextured samples of NdBa 2 Cu 3 O x (Nd123), SmBa 2 Cu 3 O x (Sm123), GdBa 2 Cu 3 O x (Gd123) and of the ternary LRE compounds like (Nd 0.33 Eu 0.33 Gd 0.33 )Ba 2 Cu 3 O x (abbreviated NEG) or (Sm 0.33 Eu 0.33 Gd 0.33 )Ba 2 Cu 3 O x (abbreviated SEG) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Surfaces of most light rare earth (LRE)-based highc superconductors were found to exhibit a pronounced nanostripe structure with a periodicity between 10 and 60 nm by means of atomic force microscopy (AFM) and scanning tunnelling microscopy (STM) investigations in ambient conditions [1][2][3][4]. The most pronounced nanostripe patterns were observed in (Nd,Eu,Gd)Ba 2 Cu 3 O x (NEG) melt-textured superconductors, which also exhibit the largest critical current densities for bulk superconductors [5].…”
mentioning
confidence: 99%